Gate oxide leakage current analysis and reduction for VLSI circuits. - Dongwoo Lee
In this paper we address the growing issue of gate oxide leakage current (Igate) at the circuit level. Specifically, we develop a fast approach to analyze the total leakage power of a large circuit block, considering both Igate and subthreshold leakage (Isub). The interaction between Isub and Igate complicates analysis in arbitrary CMOS topologies and we propose simple and accurate heuristics based on lookup tables to quickly estimate the state-dependent total leakage current for arbitrary circuit topologies. We apply this method to a number of benchmark circuits using a projected 100-nm technology and demonstrate accuracy within 0.09% of SPICE on average with a four order of magnitude speedup. We then make several observations on the impact of Igate in designs that are standby power limited, including the role of device ordering within a stack and the differing state dependencies for NOR versus NAND topologies. Based on these observations, we propose the use of pin reordering as a means to reduce Igate. We find that for technologies with appreciable Igate, this technique is more effective at reducing total leakage current in standby mode than state assignment, which is often used for Isub reduction.
Keywords: SPICE; VLSI circuits; Arbitrary CMOS topologies; Benchmark circuits; Branch-and-bound approach; Fast approach; Gate oxide leakage current analysis; Large circuit block; Leakage current reduction; Lookup tables; Pin reordering; Subthreshold leakage; Total leakage power